2006
DOI: 10.3171/ped.2006.104.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric congenital atlantoaxial dislocation: differences between the irreducible and reducible varieties

Abstract: Radiological differences in the anatomy of patients with IAAD and those with RAAD may be due to improper segmentation of the occipital and upper cervical sclerotomes in the former and dysfunction of the transverse ligament in the latter. A significantly better outcome was noted in completely dependent patients with IAAD compared with those with RAAD. Respiratory compromise was an important prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 30 publications
(24 reference statements)
2
32
0
Order By: Relevance
“…The clinical outcomes in this series are consistent with observation in experimental models that axons subjected to strain recover rapidly, both anatomically and functionally [30][31][32], and with neurosurgical series where anatomical alignment has been restored, and which show that even profound clinical deficits are recoverable [5,12,14,17,[33][34][35][36][37][38][39][40]. Improvement in pain, bulbar symptoms, ASIA index, Karnofsky index and quality of life assessment support the concept that restoration of the neutral position of the cervical spine and craniospinal junction with a neck brace decreases the deleterious effects of flexion in the setting of erstwhile abnormal movement and anatomical abnormality.…”
Section: Neurological Outcomes After Whiplash Injurysupporting
confidence: 72%
“…The clinical outcomes in this series are consistent with observation in experimental models that axons subjected to strain recover rapidly, both anatomically and functionally [30][31][32], and with neurosurgical series where anatomical alignment has been restored, and which show that even profound clinical deficits are recoverable [5,12,14,17,[33][34][35][36][37][38][39][40]. Improvement in pain, bulbar symptoms, ASIA index, Karnofsky index and quality of life assessment support the concept that restoration of the neutral position of the cervical spine and craniospinal junction with a neck brace decreases the deleterious effects of flexion in the setting of erstwhile abnormal movement and anatomical abnormality.…”
Section: Neurological Outcomes After Whiplash Injurysupporting
confidence: 72%
“…There are several variations of posterior approaches bone fusion and stabilization [4][5][6][7][8] or the transoral approach release combined with the posterior approaches bone fusion and stabilization for the malformation of the upper cervical spine [9][10][11][12]. Os odontoideum can lead to reducible or irreducible atlantoaxial dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…This has been described by Olerud 125 It should be noted that, since, there is an observed asymmetry of the facet joints among a large number of patients with OO, this might make transarticular C1-C2 stabilization difficult in this pathology, necessitating an alternative method on the abnormal side. 126 About 15 years after the introduction of transarticular C1-C2 technique, posterior C1 lateral mass and C2 pars instrumentation by means of screw-plate was introduced by Goel and Laheri in 1994. 127 Thereafter, Harms modified this technique with the application of the polyaxial screw-rod system, which eased and increased stabilization and significantly improved the outcome.…”
Section: Management Of Reducible Atlantoaxial Instability In Oomentioning
confidence: 99%
“…3 This remained the procedure of choice for many authors such as Salunke et al who have reported their experience in 2005. 126 However, to avoid any complication of this corridor, a retropharyngeal route was proposed. Later, Leng et al described the endoscopic endonasal resection of OO with fewer complications in comparison to the former route.…”
Section: History Of Surgical Intervention In Iaadmentioning
confidence: 99%
See 1 more Smart Citation